Updates on the molecular spectrum of MEFV variants in lebanese patients with Familial Mediterranean Fever - Feghali, Rudy; Ibrahim, José-Noel; Salem, Nabiha; Moussallem, Romy; Hijazi, Ghina; Attieh, Charbel; Yammine, Tony; Chebly, Alain (Frontiers in Genetics, 2025)
Familial Mediterranean Fever (FMF) is a hereditary autoinflammatory disorder, particularly present in the Mediterranean populations, and associated with pathogenic variants in the MEFV gene. This study aims to investigate the distribution of MEFV variants in a large cohort of Lebanese patients, and to explore the genotype-phenotype correlation among affected individuals. A retrospective analysis was conducted on 3,167 patients referred for MEFV sequencing at the Medical Genetics and Genomics Center(CGGM) at Saint-Joseph University of Beirut-Lebanon, from 2006 to 2023. Sanger sequencing was used to detect MEFV variants, focusing initially on hot-spot exons. Among the 3,167 patients, 46.73% (N = 1,480) carried at least one MEFV variant. The most common variants detected were M694V and V726A, both found in 28.98% of cases, followed by E148Q(27.83%) and M694I(13.98%). Moreover, Shiites and Sunni Muslims, and individuals from South and North Lebanon exhibited the highest frequency of variants. Interestingly, family history was found to be significantly higher in patients having two MEFV variants than those with one variant (p = 0.0026). The most commonly reported symptoms were fever(78%), abdominal pain(88%), joint pain(65%), and thoracic pain(46%). The genotype-phenotype correlation analysis revealed a more severe phenotype in patients carrying the M694V or V726A mutations compared to those with the homozygous E148Q genotype. This study, the largest in Lebanon, highlights the high prevalence of MEFV variants, particularly M694V and V726A, in FMF patients. Our data provide valuable insights into the genetic landscape of FMF in Lebanon and emphasize the importance of early genetic screening for a better disease management and genetic counselling.